Effect of carbonated cement paste on composite cement hydration and performance. (August 2020) - Zajac, Maciej; Skocek, Jan; Durdzinski, Pawel; Bullerjahn, Frank; Skibsted, Jørgen; Ben Haha, Mohsen
Abstract: In this work carbonated cement paste from demolished concrete recycling has been investigated as an active SCM-like component of composite cement. Carbonation of hydrated cement paste results in formation of calcium carbonate and a silica-alumina gel. The gel is found to be a pozzolanic material with high reactivity. Its composition is similar to the glass phase of siliceous fly ash and hence its impact on the resulting hydrate assemblage is comparable. However, due to the high specific surface of the gel and its structure, the pozzolanic reaction is very rapid achieving degrees of reaction of 50% after one day of reaction. The formed calcium carbonate acts as a fine filler. As a result, composite cements containing carbonated recycled cement paste are characterized by a rapid strength gain and a dense microstructure already at early age.